APPLICATION OF MISE-A-LA-MASSE METHOD FOR DETERMINING WATER DISTRIBUTION IN A LIMITED AREA (ITB PHYSICS PARK) - Indra Permana, Deni
The geoelectrical method is a method that uses the principle of electric current flow in investigating the subsurface structure of the earth. This method can be used for shallow exploration which has a depth of about 300-500 m, for example for groundwater exploration. Mise-A-La-Masse is a geoelectric method that uses casing wells as electrodes buried in the earth. Mise-A-La-Masse measurements were carried out at the ITB Physics Park. Measurements were made using 49 points with a square measurement pattern with a measurement area of 36 m2. The purpose of this study was to determine the prospect area for the distribution of water in ITB Physics Park. The data have been processed, then do inversion to determine changes in resistivity with depth, modeling produced is 3 layers. The inversion results show that water can be found in the first and second layers up to a depth of 56.35 m. In the third layer, water is not found and consists of clay, sand, and gravel.